Quality of Life Among Adults with Repaired Tetralogy of Fallot: a Literature Review - Rodrigues, C (2021)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart defect. Survival into adulthood is currently expected following surgical repair, leading to a growing population of adults with repaired TOF. In this literature review, we aim to summarize the current state of knowledge on the quality of life of adults with repaired TOF. A search was conducted on PubMed and results were reviewed for articles published between January of 2010 and June of 2020. Search terms included "Tetralogy of Fallot", "repaired", "adults" and "quality of life". For the subjective health status evaluation, most published studies used Short-Form-36. Most studies agree that physical complex status is poorer for adult patients with repaired TOF than for controls. Mental complex status was also lower. Patients reported similar satisfaction with their lives and levels of social participation. Most patients had a college or university degree. Higher education, male gender and having a partner were positively associated with being employed. Studies found no difference in the proportion of patients that are married or living with a partner, compared to control groups. Patients operated for TOF have a lower reproduction rate compared with the background population. A consistent finding of these studies is abnormal physical parameters compared to psychosocial issues. The diverse needs of adults with repaired TOF require a multidisciplinary care, that takes into consideration all aspects that affect their quality of life. Despite abnormal physical functional status, it is reassuring that most adult patients with TOF lead independent and productive lives.